IMPLEMENTASI PENDIDIKAN KARAKTER DALAM MEMBENTUK PERILAKU SISWA SEKOLAH DASAR - Rizky, Alvina Elysia; Dwi Tasya Khusnawati; Muhammad Deni Saputra; Neiska Zahra Ananda handoko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Character education is an essential element of elementary education because it guides students to behave in accordance with social, religious, and moral principles. This study describes the implementation of character education and its contribution to student behavior at SD Negeri 3 Metro Barat. A descriptive qualitative design was used, with data obtained through interviews, observation, and documentation involving the principal, teachers, and students. Data processing comprised reduction, presentation, and conclusion drawing, while credibility was examined through source and technique triangulation. The results show that character values are cultivated through classroom instruction, repeated habituation, teacher role modeling, and a school culture integrated with the Seven Habits of Great Indonesian Children Program. The activities consist of reading holy scriptures before lessons, Friday Blessing, Friday Charity (Jumat Infak), Clean Friday (Jumat Bersih), congregational Duha prayer, the Jumpangsi creative performance, and the 5S culture (Smile, Greet, Salute, Politeness, and Courtesy). The principal values emphasized are religiosity, discipline, responsibility, honesty, care, cooperation, and respectful behavior. These programs have encouraged positive changes in students, although their outcomes remain less than optimal because behavior is also shaped by family circumstances, peer interaction, and digital-media exposure. Continuous cooperation among schools, parents, and the community is therefore required to strengthen students' character development.